(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
The present writing deals with darkness as bodyscenical, darkness as problematization that inhabits the Western Theater and its ideal of lightning on stage. The Western body-thought, accostumed to the enlightnment brought by Religion, Science and Art, separates everything that comes from light, everything that gives light, from that which, on an absolutely opposite pole, reveals darkness. In works of visual art, in works of sound art, create-itself-in-resistence poems-dramaturgies, that is, scenical works of art. The West, as the wordly stage of Reason and Theater, constitutes itself as poem-dramaturgy and places itself as space-time-of-scene, at the same time, light and darkness.